Enhancing multi-sectoral collaboration in health: the open arena for public health as a model for bridging the knowledge-translation gap - Pradier, Christian; Balinska, Marta A.; Bailly, Laurent (Frontiers in Health Services, 2023)
Effective public health interventions at local level must involve communities and stakeholders beyond the health services spectrum. A dedicated venue for structured discussion will ensure ongoing multi-sectoral collaboration more effectively than convening ad hoc meetings. Such a venue can be created using existing resources, at minimal extra cost. The University Hospital in Nice (France) has established an Open Arena for Public Health which can serve as a model for promoting collaborative partnerships at local level. The Arena has been successful in implementing sustainable interventions thanks to a set of principles, including: non-hierarchical governance and operating, fair representation of stakeholders, consensus as to best available evidence internationally and locally, policy dialogues: open, free-flowing discussions without preconceived solutions, and an experimental approach to interventions.